Factors affecting halal purchase intention: Case study in Indonesia - Wardhani, Dona Setiya; Tilaar, Ovelia Regina Pratiwi; Saudi, Mohd Haizam Mohd; Hasim, Muhammad Asyraf (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to evaluate and determined the relationship of selected factors towards customer purchase intention on Halal products. Recently there are a positive indicator that shows Muslim have started to carefully look for a Halal product for consumption. Governments contributes to the setting up of the Halal hub for Muslim consumer. The challenge is to get the Muslim attraction in making decision tom purchase since there are too many options available for them to choose. Awareness and religiosity are among the two factors selected to measure the impact of both towards purchase intentions. 200 respondents participated in the survey exercise. Respondent was chosen on based on purposive basis. Data collection took over 5 days’ period for compilations. All data were accepted and valid for data analysis. The results indicate that both factors are important towards customer purchase intentions. Marketers need to focus on both factors so that it can helps them to design the marketing campaign and promotions. Business owner or service provider ion Halal industry should take note on the findings and realign their business marketing strategy towards enhancing purchase intentions.